Spatial distribution of tropical estuarine nematode communities in Sarawak, Malaysia (Borneo). - Cheng, Ann Chen; Shabdin, Mohd Long; Norliana, Rosli (Researchgate, 2012)
Limited information is available on marine nematode assemblages from Malaysian waters. Field sampling was conducted at the river mouths of 10 estuaries along the coastline of Sarawak (Malaysia) in Borneo to determine the distribution pattern of marine nematode assemblages. Physico-chemical parameters were also recorded to determine if distribution of nematodes was correlated with salinity, temperature, dissolved oxygen, and pH. Overall, the sampled sites were characterised by low density and low diversity of nematodes. Multidimensional scaling (nMDS) and dendrogram showed high dissimilarity in species distribution. BioEnv recorded a low positive correlation between marine nematode species densities and environmental parameters (pH and particle fraction: silt). Functional feeding group (FFG) changed from the north to south suggesting adaption by marine nematodes to food availability. Daptonema tenuispiculum, Sabatieria praedatrix group and Terschellingia longicaudata were dominant in several study sites. In conclusion, a total number of 49 species of marine nematodes were recorded (excluding two freshwater species from the order Dorylaimida). Low densities and diversities together with the proportion of the functional feeding groups between the 10 study sites indicated a stressful environment for nematodes and nematode communities could potentially be used for future pollution assessment of estuarine habitats.